2016
DOI: 10.1108/aaouj-09-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Profiling information-seeking behaviour of distance learning students in Wawasan Open University

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…Majority of the respondents confirmed that they had not received any training in using Internet or library resources, This situation is not uncommon in other libraries as many Sri Lankan researchers (Gunasekera 2010, Jezeel and Dehigama 2016, Karunarathne 2015, Premarathne 2017, Ranawella and Rajapaksha 2017 as well as international researchers (Head and Eisenberg 2010, Kumar 2013and Vighnarajah 2016 have identified that the students are not aware of the available library resources and services. Head and Eisenberg (2010) comments that there is a gaping hole in the understanding of the students on how the vast range of resources provided by the libraries could meet their need for trusted information.…”
Section: Discussionmentioning
confidence: 98%
“…Majority of the respondents confirmed that they had not received any training in using Internet or library resources, This situation is not uncommon in other libraries as many Sri Lankan researchers (Gunasekera 2010, Jezeel and Dehigama 2016, Karunarathne 2015, Premarathne 2017, Ranawella and Rajapaksha 2017 as well as international researchers (Head and Eisenberg 2010, Kumar 2013and Vighnarajah 2016 have identified that the students are not aware of the available library resources and services. Head and Eisenberg (2010) comments that there is a gaping hole in the understanding of the students on how the vast range of resources provided by the libraries could meet their need for trusted information.…”
Section: Discussionmentioning
confidence: 98%
“…In the context of WOU distance learners, Vighnarajah and Santhiram (2014)'s qualitative study has also found that there is a poor engagement between distance learners with library services which can potentially lead to learners experiencing a sense of isolation in the overall university learning experience. This is supported by one of Vighnarajah et al (2015) survey study findings which highlighted that 19 percent of the sample size (distance learners) were not able to locate information, while 12 percent of them were not aware that relevant information (printed or digital copies) were available in the library. They further recommended for the library to provide proper guidance to distance learners in searching for information.…”
Section: Aaouj 122mentioning
confidence: 69%
“…Sin embargo, los criterios que utilizan para seleccionar las fuentes de información en sus trabajos académicos no son los adecuados (Tury et al, 2015). También, la literatura plantea que los estudiantes presentan poco dominio en el proceso de búsqueda de información y el uso de ésta (Ali Hassan et al, 2016). Esta falta de destrezas en la búsqueda de información se asocia con HETS Online Journal, Volume 13(2), Spring 2023 la ansiedad bibliotecaria experimentada por los estudiantes universitarios (Latham y Gross, 2007;Van Kampen-Breit & Cooke, 2015).…”
Section: Resumen De La Literatura Revisadaunclassified
“…Según lo antes expuesto, las destrezas de información jugarían un papel esencial en el rol del estudiante en los entornos de educación a distancia. Ali Hassan et al (2016), por ejemplo, encontraron que los estudiantes a distancia que demostraron poco dominio en la búsqueda efectiva de información académica presentaron sentimientos de aislamiento. Budiman (2016) identificó que uno de los principales factores para darse de baja en entornos de educación a distancia es precisamente que el estudiante experimente aislamiento en su proceso de aprendizaje.…”
Section: Resumen De La Literatura Revisadaunclassified